2019
DOI: 10.1186/s12974-019-1626-x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct migratory pattern of naive and effector T cells through the blood–CSF barrier following Echovirus 30 infection

Abstract: Background: Echovirus 30 (E-30) is one of the most frequently isolated pathogens in aseptic meningitis worldwide. To gain access to the central nervous system (CNS), E-30 and immune cells have to cross one of the two main barriers of the CNS, the epithelial blood-cerebrospinal fluid barrier (BCSFB) or the endothelial blood-brain barrier (BBB). In an in vitro model of the BCSFB, it has been shown that E-30 can infect human immortalized brain choroid plexus papilloma (HIBCPP) cells. Methods: In this study we inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…Preliminary observations made with the Th cell subsets used in the present study confirm involvement of GPCR signaling in the diapedesis of all Th subsets across BLEC monolayers. Furthermore, our previous studies have shown that addition of exogenous CXCL12 to the CSF side increased T-cell migration across HIBCPP monolayers [31,68,69]. These data support the additional role for GPCR signaling in the migration of effector Th cell subsets across the BBB and BCSFB.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Preliminary observations made with the Th cell subsets used in the present study confirm involvement of GPCR signaling in the diapedesis of all Th subsets across BLEC monolayers. Furthermore, our previous studies have shown that addition of exogenous CXCL12 to the CSF side increased T-cell migration across HIBCPP monolayers [31,68,69]. These data support the additional role for GPCR signaling in the migration of effector Th cell subsets across the BBB and BCSFB.…”
Section: Discussionsupporting
confidence: 74%
“…Both BLECs and HIBCPP cells have previously been shown to phenocopy characteristics of a functional BBB and BCSFB, respectively. BLECs and HIBCPP form mature adherens and tight junctions, show low permeability to small molecular tracers, establish high electrical resistance, show functional expression of characteristic transporters and efflux pumps and display apical/basolateral polarity [22][23][24][25][26][27][28][29][30][31]. In addition, both human brain barrier models were previously shown by us and others to show cytokine inducible expression of adhesion molecules and to be suitable for studying immune cell trafficking across the BBB and BCSFB in vitro [26,28,[32][33][34].…”
Section: Introductionmentioning
confidence: 95%
“…A reliable in vitro model that uses an immortalized and widely available cell line would help to standardize the experiments and results surrounding BCB research. HIBCPP cells have recently been identified as a consistent model of the BCB, and several publications have utilized these cells as a barrier model [ 5 , 6 , 7 ]. The HIBCPP cell line was established in 2005 from a human choroid plexus papilloma [ 8 ] and has been characterized in several studies that indicate that HIBCPP cells have many critical functional characteristics of choroid plexus epithelial cells—namely, the ability to polarize and express marker proteins to match choroid plexus epithelial cells in vivo [ 5 , 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the enteroviruses, Echovirus-30 (E-30) is a nonpolio enterovirus (NPEV) species B, responsible for extensive global outbreaks of meningitis in children [ 8 , 9 , 10 ], and which can result in mild symptoms, but might also rapidly evolve towards a lethal outcome [ 11 , 12 ]. Several clinical studies revealed that enterovirus infection of the CNS results in increased levels of inflammatory chemokines within the cerebrospinal fluid (CSF), including INF-γ , CXCL12 , CXCL10 , IL-6 , IL-1 and TNF-α , which increase the influx of neutrophils and T cells into the brain parenchyma [ 13 , 14 , 15 ]. However, the underlying mechanisms used by these viruses to enter the brain and induce CNS inflammation are not fully understood yet.…”
Section: Introductionmentioning
confidence: 99%